Dissecting the role of comS-independent srf expression on multicellular differentiation and competence development in Bacillus subtilis - Miercke, Sarah; Knepper, Jan-Philipp; Dreisewerd, Klaus; Mascher, Thorsten (Frontiers in Microbiology, 2026)
In its natural soil habitat, B. subtilis regularly encounters fluctuating conditions that require adaptive survival strategies, including the production and secretion of antimicrobial compounds. One such compound, surfactin, play a central role in multicellular differentiation processes such as biofilm formation, swarming, and competence development. Competence and surfactin biosynthesis are transcriptionally co-regulated via the quorum sensing-mediated activation of the srfAABCD operon, which contains comS in a distinct open reading frame overlapping with srfAB. This study aimed at uncoupling competence from surfactin production by introducing targeted stop mutations in comS to selectively disrupt competence without affecting surfactin synthesis. For this, we introduced single nucleotide polymorphisms (SNPs) that preserved the srfAB codons, while simultaneously introducing a premature stop codon in comS. The effects on competence development were assessed using luciferase-based reporter assays monitoring the ComS-dependent expression of comK and comGA expression. Surfactin production was analyzed by mass spectrometry imaging and phenotypic assays examining the impact on multicellular behavior. Our findings demonstrate that the generated point mutations severely reduce competence gene expression, measured via PcomK and PcomGA activity, to levels comparable with a full comS deletion, while leaving multicellular behaviors such as biofilm and pellicle formation, as well as swarming and sliding motility, unaffected. Thus, ComS is specifically essential for competence development but dispensable for other surfactin-mediated multicellular processes and not involved in structuring biofilms. Taken together, our results demonstrate that it is possible to genetically decouple competence from other developmental pathways in B. subtilis.